SPECTROPHOTOMETRY DETERMINATION OF PLATINUM(II) FROM PLATINUM BASED CISPLATIN AND CARBOPLATIN ANTICANCER INJECTIONS - Khuhawar, M. Y.; Arain, G. M.; Shah, A. (The Nucleus, 2020)
Spectrophotometric method has been developed for the determination of platinum(II) after derivatization with bis(2-hydroxynaphtaldehyde) ethylendiimine (H2HN2en). The complex was extracted in chloroform at pH 8. The absorbance was measured at 355 nm.The linear calibration curve was obtained with 1-5Î¼g/ml platinum. The platinum was determined from cisplatin and carboplatin injections with relative standard deviation (RSD) of 0.7 to 2.2%. Copper(II), nickel(II) and palladium(II) also reacted with H2HN2en, and absorbed at 390 nm , 328 nm and 330 nm respectively. The copper, nickel, cobalt and iron when added at the concentration similar to platinum did not affect the determination of platinum with relative error within 5%.